APPLICATION OF POLYMER MATERIAL IN HOUSING AND UTILITIES SECTOR CITY (Municipal economy of cities. Series: «Economy science», 2013)
The problem questions rational use of polymer composites in municipal city. The feasibility and effectiveness of the secondary polymer composites.